Temporal trends in living kidney donation in France between 2007 and 2017. Issue 4 (28th November 2019) - Gaillard, François; Jacquemont, Lola; Roberts, Veena; Albano, Laetitia; Allard, Julien; Bouvier, Nicolas; Buchler, Mathias; Titeca-Beauport, Dimitri; Couzi, Lionel; Delahousse, Michel; Ducloux, Didier; Durrbach, Antoine; et al.
Abstract: Background: Long-term studies have demonstrated a slight increased risk for end-stage renal disease (ESRD) for living kidney donors (LKD). In France, living kidney donation doubled within the past 10 years. We investigated the change in characteristics of LKD between 2007 and 2017 and the adequacy of follow-up. Methods: Data were obtained from the national registry for LKD. We compared characteristics of LKD between two study periods: 2007–11 and 2012–17, and stratified donors by age and relation to recipient. We aggregated four characteristics associated with higher ESRD risk [young age, first-degree relation to recipient, obesity, low glomerular filtration rate (GFR) for age] in a single risk indicator ranging from 0 to 4. Results: We included 3483 donors. The proportion of unrelated donors >56 years of age increased significantly. The proportion of related donors <56 years of age decreased significantly. The body mass index and proportion of obese donors did not change significantly. The proportion of donors with low estimated GFR for age decreased significantly from 5% to 2.2% (P < 0.001). The proportion of donors with adequate follow-up after donation increased from 19.6% to 42.5% (P < 0.001). No donor had a risk indicator equal to 4, and the proportion of donors with a risk indicator equal to 0 increased significantly from 19.2% to 24.9% (P < 0.001). Conclusions: An increase in living kidney donation in France does not seem to be associated with the selection of donors at higher risk of ESRD and the proportion of donors with adequate annual follow-up significantly increased.